2016
DOI: 10.1007/s00436-016-4951-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological assessments of human Blastocystis spp. in experimentally infected immunocompetent and immunosuppresed mice

Abstract: Blastocystis spp., one of the most common parasites colonizing the human intestine, is an extracellular, luminal protozoan with controversial pathogenesis. The host's immune response against Blastocystis spp. infection has also not been defined yet. Therefore, this research aimed to assess the potential pathogenicity of this parasite and its ability to modulate the immune response in experimental infected immunocompetent and immunosuppresed mice. These results demonstrated that the infected immunosuppressed mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…was further proven with the evidence of the formation of cysteine proteases [ 22 ]. In another study, intestinal cells were found to exhibit low level of IgA and increased level of pro-inflammatory cytokines in the presence of Blastocystis infection [ 23 , 24 ]. Even though numerous in vitro studies have been carried out to associate Blastocystis with colorectal cancer, there were no studies conducted thus far using cancer-induced rat models to validate this association.…”
Section: Introductionmentioning
confidence: 99%
“…was further proven with the evidence of the formation of cysteine proteases [ 22 ]. In another study, intestinal cells were found to exhibit low level of IgA and increased level of pro-inflammatory cytokines in the presence of Blastocystis infection [ 23 , 24 ]. Even though numerous in vitro studies have been carried out to associate Blastocystis with colorectal cancer, there were no studies conducted thus far using cancer-induced rat models to validate this association.…”
Section: Introductionmentioning
confidence: 99%
“…A similar picture with mild inflammatory reaction was noticed in mice inoculated by isolates derived from asymptomatic carriers included in our study. On the other hand, isolates from symptomatic patients have been observed, in many studies, to cause more severe and intense pathological changes with mucosal sloughing, intense inflammatory cells infiltration, and parasite infiltration of lamina propria in mice [28,30,44,49] and rats [6,27,31,55] . In addition, Hussein et al [31] and Abaza et al [6] reported the induction of a more severe degree of pathological change with polypoid projections in colonic mucosa of rats infected by symptomatic isolates, that the authors referred to as precancerous polyps.…”
Section: Discussionmentioning
confidence: 99%
“…infected immunosuppressed mice produced significantly more IFN-γ than infected immunocompetent hosts, as in previous studies on the invasion of Blastocystis spp. [ 44 ].…”
Section: Discussionmentioning
confidence: 99%